If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -4y = -8 Solving -6x + -4y = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -6x + -4y + 4y = -8 + 4y Combine like terms: -4y + 4y = 0 -6x + 0 = -8 + 4y -6x = -8 + 4y Divide each side by '-6'. x = 1.333333333 + -0.6666666667y Simplifying x = 1.333333333 + -0.6666666667y
| -32=2(4+6x)-3 | | a+2b-5a-(-b)=0 | | 14(x-5)=-7-7 | | -32=2(4+6)-3 | | x+3y=8 | | 10t=-26 | | 2(x+5)=22 | | 4a-a+3a=0 | | -4x+9x-3=-13 | | 6x-3y-5x+3y= | | 5x-a=2ax+7 | | 16-10x=21-2x | | 3x^2-5x+5=0 | | 6x+5=7x+16 | | 12m=7 | | n+31=51 | | 16-5s=31 | | n+10=15 | | 5m+74=34 | | 13-2v=7 | | .66-3y=5.66 | | 16+1.25x=10 | | -2x+y=10 | | 6.2x+2=5.2x-4 | | 2.5y=36 | | 2.5y=37 | | 7x+21=4x+102 | | 88-7x=38x-23 | | 4x+12=9x+13 | | 130-8x=9x+23 | | 14x=84+7x | | -7x-10=7x-122 |